(untitled) (Perner’s Contacts, 2009)
Income elasticity measures extent of demand change in dependence on changes of customers income. It is important tool of transport economist for analysis of transport demand. Regression a correlation analysis can be used by examination of relation between income (wages of employees) and demand for public transport, next calculation of elasticity coefficients will be made as well.